Ijtihad dan Otoritas Keilmuan dalam Ushul Fikih: Antara Tradisi Normatif dan Kontekstualisasi Hukum Islam - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study examines the relationship between ijtihad and scholarly authority within ushul al-fiqh, focusing on the tension between normative tradition and contemporary contextualization of Islamic law. It argues that ijtihad has always been governed by epistemological frameworks that define legitimate authority through methodological competence and hierarchical expertise. Classical ushul al-fiqh regulated ijtihad to prevent arbitrariness, while modern contexts demand adaptive reasoning to address complex social realities. Through comparative analysis, the study shows that contemporary ijtihad requires reconstructing scholarly authority toward collective, institutional, and maqāṣid-oriented models. This approach preserves methodological integrity while enabling Islamic law to remain dynamic, credible, and responsive to modern challenges. Keywords: Ijtihad, Scholarly Authority, Ushul al-Fiqh